Anterior cerebral artery embolism during thrombectomy increases disability and mortality. (8th May 2018) - Chalumeau, Vanessa; Blanc, Raphaël; Redjem, Hocine; Ciccio, Gabriele; Smajda, Stanislas; Desilles, Jean-Philippe; Botta, Daniele; Escalard, Simon; Boisseau, William; Maïer, Benjamin; Labreuche, Julien; Obadia, Mickaël; et al.
Abstract : Objective: During thrombectomy, thromboembolic migration in previously unaffected territory may occur and is not systematically notified. We report our data on the incidence, predictors, and clinical outcome of anterior cerebral artery emboli (ACAE). Methods: From a prospectively collected thrombectomy database of consecutive patients with anterior circulation stroke between January 2012 and December 2016, 690 angiographic images were analyzed to assess ACAE. The primary outcome was a favorable outcome, defined as a 3 month modified Rankin Scale score of 0–2 or equal to the pre-stroke score. Results: ACAE occurred in 65 patients (9.4%; 95% CI 7.2% to 11.6%). Internal carotid artery occlusion (tandem or terminal), Alberta Stroke Program Early CT Score <7, increasing number of passes, and use of stent retriever alone (compared with distal aspiration alone or combined with stent retriever) were found to be independent predictors of ACAE. Compared with patients without ACAE, patients with ACAE had lower rates, with an adjusted OR (95% CI) of 0.48 (0.25 to 0.92; P=0.027) for favorable outcome and 0.49 (0.25 to 0.96; P=0.038) for early neurologic improvement. ACAE was significantly associated with a higher mortality (adjusted OR 1.93; 95% CI 1.03 to 3.61; P=0.039) and intracranial hemorrhagic complications (adjusted OR 2.45; 95% CI 1.33 to 4.47; P=0.004). Despite a successful reperfusion modified Thrombolysis in Cerebral Infarction score of 2b–3 at the end of the procedure, a favorable outcome was reached in 30% of patients with ACAE compared with 52.4% in the other patients (OR 0.39; 95% CI 0.19 to 0.78; P=0.008). Conclusions: Procedural ACAE was not an uncommon condition, and was associated with increased mortality and disability rates, regardless of the success of reperfusion.